Reduce - Edwards, Mike.; Edwards, Mike; Prenthieks, Erik (California: AIMS Multimedia, 2000)
This program explains how over-packaged and disposable items add to the trash pile and waste precious energy. It shows how buying better-made things and thing better care of the things we already have makes them last longer.
Narrator : Mike Edwards.
Keywords: Environmental protection